Analysis of the disappearance and loss of soil in the European union caused by elements of anthropogenic and natural influences - Norac-Kevo, Ivana; Kalambura, Sanja (Crisis Management Days, 2024)
Soil is often mistakenly considered a renewable resource, but due to the very long time span of the formation and regeneration processes, it is in fact a non-renewable and limited resource. Poor soil management and the loss of its fertility jeopardies not only current production capacities, but also those of future generations. Only 2-3 centimeters of soil are created in 1000 years, and 33% of the soil on our planet is currently affected by degradation processes which, according to the FAO, fall into the category of severe degradation. Worldwide, 50,000 km2 of soil is lost every year. The landscape in many areas also indicates that the interaction of climate, topography, soil characteristics and human activities has led to unsustainable development in the short and medium term. The main factors affecting the rate of soil erosion by water are precipitation, soil type, topography, land use and land management. The following data is used to estimate soil loss: erosivity of precipitation, erodibility of soil, land management and topography. Using this universal formula, it was determined that the average rate of soil loss in erosion-prone soils in the European Union (agricultural, forestry and semi-natural areas) is 2.46 tonnes per hectare per year, resulting in a total soil loss of 970 megatonnes per year. The highest annual soil loss rates were observed in the Mediterranean regions, while lower values are predicted for Scandinavia and the Baltic states. The highest average annual soil loss rate (at country level) is recorded in Italy (8.46 tonnes/ha), followed by Slovenia (7.43 tonnes/ha) and Austria (7.19 tonnes/ha), which is due to the combination of high erosive precipitation and steep topography (steep and long slopes). The average soil loss rates in other Mediterranean countries (Spain, Greece, Malta and Cyprus) are also higher than the European average. The lowest average annual soil loss rates were found in Finland (0.06 tonnes/ha), Estonia (0.21 tonnes/ha) and the Netherlands (0.27 tonnes/ha). The Republic of Croatia has an annual soil loss rate of 3.16 t/ha. Soil loss due to water erosion is expected to increase by 13–22.5 % in the EU by 2050. Changes in future soil erosion rates will be determined by climatic conditions, land use patterns, socio-economic development, farmers' decisions and agro-ecological policies. According to some climate change scenarios, soil loss could affect 84% of the area and erosion rates could reach 45%. The paper provides a detailed analysis of the indicators and causes of degradation and the potential consequences for humanity.